Novel poly(vinylidene fluoride-trifluoroethylene)/poly(ethylene oxide) blends for battery separators in lithium-ion applications - Costa, C. M. (2013)
Polymer blends based on poly(vinylidene fluoride-trifluoroethylene)/poly(ethylene oxide), P(VDF-TrFE)/PEO for Li-ion battery separators applications have been prepared through solvent casting technique. The microstructure, hidrophilicity and electrolyte uptake strongly depend on PEO content within the blend. The best value of ionic conductivity at room temperature was 0.25 mS.cm-1 for the 60/40 membrane. The membranes are electrochemically stable.